Peranan, pengaruh dan potensi Wattpad terhadap budaya membaca novel di kalangan rakyat Malaysia / Mohd Syuhaidi Abu Bakar and Nur Syuhaidah Ayub - Abu Bakar, Mohd Syuhaidi; Ayub, Nur Syuhaidah (2019)
Fostering a culture of reading and writing can be done on many platforms. Wattpad is one of them. It is a website designed for new authors and readers looking for a novel, free literary content. However, in Malaysia, this platform is still not being explored enough. This paper has qualitatively analyzed the role, influence and potential of Wattpad in fostering reading culture among Malaysians. 10 informants were interviewed and discussions were transcribed verbatim and imported into ATLAS.ti 4.2 software program. It was found that Wattpad had a significant role, influence and potential in fostering a culture of reading and writing in this country. It can be concluded that beyond the school and family setting, Internet at large can also play a role in fostering reading and writing culture.